2010
DOI: 10.1007/s00330-009-1693-y
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion computed tomography evaluation of angiogenesis in liver cancer

Abstract: CT perfusion imaging can quantitatively assess the blood supply and its distribution in liver cancer. TBF or HAP may be a useful parameter in assessing angiogenesis of liver cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…For PS, sensitivity was 71.4% and specificity was 57.1% if the cut-off point was set at 7.31 mL/min/100 g. The possible reason was that chemotherapeutics might be prone to pass the incomplete vessel of the tumour and to play an antitumoural role if PS was high. In the meantime, new tumour vessels were augmented, the richness of the tumour vessels increased, and thus the oxygenation status of the tumour was high, which led to good response to synchronous radiochemotherapy in the early phase [29,30]. The results of our study were inconsistent with the result acquired by Wang et al [2] who demonstrated that there was no significant difference in baseline PS between responders and non-responders, and that the tumour with a high PS had a short median overall survival period.…”
Section: Discussionmentioning
confidence: 99%
“…For PS, sensitivity was 71.4% and specificity was 57.1% if the cut-off point was set at 7.31 mL/min/100 g. The possible reason was that chemotherapeutics might be prone to pass the incomplete vessel of the tumour and to play an antitumoural role if PS was high. In the meantime, new tumour vessels were augmented, the richness of the tumour vessels increased, and thus the oxygenation status of the tumour was high, which led to good response to synchronous radiochemotherapy in the early phase [29,30]. The results of our study were inconsistent with the result acquired by Wang et al [2] who demonstrated that there was no significant difference in baseline PS between responders and non-responders, and that the tumour with a high PS had a short median overall survival period.…”
Section: Discussionmentioning
confidence: 99%
“…Moderately differentiated and poorly differentiated HCCs are usually considered to be hypervascular, while well-differentiated tumors can be hypovascular (27). Some authors found that there was no significant difference in perfusion parameters between well to moderately differentiated and poorly differentiated HCC (22,28). However Sahani et al (24) observed that the perfusion of well-differentiated HCC was distinct from those of moderately and poorly differentiated HCC.…”
Section: Perfusion Imaging For Detection Of Hepatocellular Carcinomamentioning
confidence: 99%
“…A suitable biomarker may increase the probability of detecting a true antitumor effect, as well as predict clinical activity after treatment in a short course. Computed tomography (CT) imagingbased therapy monitoring has gained an important role in oncologic imaging [9][10][11]. Tumour size change in conventional CT has been widely used to assess antitumor response [11][12][13].…”
Section: Introductionmentioning
confidence: 99%